-x+35=3x+11

Simple and best practice solution for -x+35=3x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+35=3x+11 equation:


Simplifying
-1x + 35 = 3x + 11

Reorder the terms:
35 + -1x = 3x + 11

Reorder the terms:
35 + -1x = 11 + 3x

Solving
35 + -1x = 11 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
35 + -1x + -3x = 11 + 3x + -3x

Combine like terms: -1x + -3x = -4x
35 + -4x = 11 + 3x + -3x

Combine like terms: 3x + -3x = 0
35 + -4x = 11 + 0
35 + -4x = 11

Add '-35' to each side of the equation.
35 + -35 + -4x = 11 + -35

Combine like terms: 35 + -35 = 0
0 + -4x = 11 + -35
-4x = 11 + -35

Combine like terms: 11 + -35 = -24
-4x = -24

Divide each side by '-4'.
x = 6

Simplifying
x = 6

See similar equations:

| 36+8a=(3a+1) | | (3x-4)+(X)=148 | | -2+2x=5x-20 | | 7x+9=49+3x | | 25x^2-24x-9=-7x^2+12-18 | | 6=x/65 | | 2x-6=7x+14 | | 4x+14=-8x-2(7-4x) | | 36+8a=3(3a+1) | | -5x-9y=45 | | x-6=2x+5 | | 5-7(8y+6)= | | 11(2-9)+99-10(2)= | | 13k-130=201 | | 3x+5=-19+7x | | x-5=2x+5 | | -37/16=v/32 | | x-5(27-x)= | | 12x^2=-10x+5 | | 5(n+3)+11n=2+3n | | x(4x-5)-3=3 | | 5+6x=3x+29 | | X-4(x+13)= | | Inx+Inx^8=9 | | Log(x-1)+log(x+1)=0 | | 5(3x)=4 | | 9x=12x+1 | | -3x+32=5 | | 5x+1=4x+10 | | 3x+12=-80-10x | | 11x-7=10x+4 | | 15+3x=9+6x |

Equations solver categories